THE STUDY OF URBANIZATION PATTERNS AND THEIR IMPACTS ON ROAD SAFETY - P. Iamtrakul; K. Hokao (International Association of Lowland Technology, 2012)
Recently, Bangkok and its vicinities have been growing and become megacity. One of the main affects of land use and transportation interaction is the enormous societal loss in term of road traffic casualties. It requires a tool for safety vision as a proactive and integral approach to coordinate transportation and land use planning decision. This study explores the impacts of urbanization pattern on road safety base on three main driving factors which are physical conditions, economic opportunities and demographic growth together with plans and policies. The results could be compared with the different deterioration of safety level base on an application of severity approach and demonstrated by spatial techniques of aerial photo and geographical information system. With this tool, it is enable for more coordination among different stakeholders for improving road safety situation on an influence of the negative effects of sprawling development while promote sustainable transportation.